Role of Social Media in the Successful Implementation of Business User Data Management - Nurbasari, Anny; N. Lukiyanova, Marina; Thanh Nguyen, Phong; A. Shichiyakh, Rustem; Shankar, K. (Opción, 2019)
The associate degree of the section ever-growing people used social me- dia on a frequently, Information of a social media analyzed in arose many various sciences. The social media analysis technique consists of four steps data representation, system, composition, and assessment. the huge deal of literature on the challenges and problem with specified knowledge analysis methods, there is very little analysis of the stages of data finding, group and arrangement. the counter their discrepan- cy, our self-came to a collaborative extended and structured literature analysis. Social networking describes the phenomenon found in dem- ocratic and self-communicating net sites such as Facebook, MySpace, YouTube where members and participants share their personal lives, discuss, hope, dream, and even act. The ideas of others and ideas of wonder. Online communities represent a growing range of communi- ties in the marketplace where participants give and exchange data on manufacturers, services or common interests. Brands are, or are, social.